Removal of Manganese Ions (Mn2+) from a Simulated Wastewater by Electrocoagulation/ Electroflotation Technologies with Stainless Steel Mesh Electrodes: Process Optimization Based on Taguchi Approach - H. Salman, Rasha (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
This study depicts the removal of Manganese ions (Mn2+) from simulated wastewater by combined electrocoagulation/ electroflotation technologies. The effects of initial Mn concentration, current density (C.D.), electrolysis time, and different mesh numbers of stainless steel screen electrodes were investigated in a batch cell by adopting Taguchi experimental design to explore the optimum conditions for maximum removal efficiency of Mn. The results of multiple regression and signal to noise ratio (S/N) showed that the optimum conditions were Mn initial concentration of 100 ppm, C.D. of 4 mA/cm2, time of 120 min, and mesh no. of 30 (wire/inch). Also, the relative significance of each factor was attained by the analysis of variance (ANOVA) which indicates that the percentage of contribution followed the order: time (47.42%), C.D. (37.13%), Mesh number (5.73%), and Mn initial Conc. (0.05%). The electrolysis time and C.D. were the most effective operating parameters and mesh no. had a fair influence on Mn removal efficiency, while the initial conc. of Mn. had no significant effect in the studied ranges of control factors. Regression analysis (R2= 90.16%) showed an acceptable agreement between the experimental and the predicted values, and confirmation test results revealed that the removal efficiency of Mn at optimum conditions was higher than 99%.